Intranasal 15d-PGJ2 inhibits the growth of rat lactotroph pituitary neuroendocrine tumors by inducing PPARγ-dependent apoptotic and autophagic cell death - Li, Zongyang; Chen, Lei; Zhang, Di; Huang, Xianjian; Yang, Jihu; Li, Weiping; Wang, Chuanfang; Meng, Xiangbao; Huang, Guodong (Frontiers in Neuroscience, 2023)
PPARγ agonists have been reported to induce cell death in pituitary neuroendocrine tumor (PitNET) cell cultures. However, the therapeutic effects of PPARγ agonists in vivo remain unclear. In the present study, we found that intranasal 15d-PGJ2, an endogenous PPARγ agonist, resulted in growth suppression of Fischer 344 rat lactotroph PitNETs induced by subcutaneous implantation with a mini-osmotic pump containing estradiol. Intranasal 15d-PGJ2 reduced the volume and weight of the pituitary gland and the level of serum prolactin (PRL) in rat lactotroph PitNETs. 15d-PGJ2 treatment attenuated pathological changes and significantly decreased the ratio of PRL/pituitary-specific transcription factor 1 (Pit-1) and estrogen receptor α (ERα)/Pit-1 double-positive cells. Moreover, 15d-PGJ2 treatment induced apoptosis in the pituitary gland characterized by an increased ratio of TUNEL-positive cells, cleavage of caspase-3, and elevated activity of caspase-3. 15d-PGJ2 treatment decreased the levels of cytokines, including TNF-α, IL-1β, and IL-6. Furthermore, 15d-PGJ2 treatment markedly increased the protein expression of PPARγ and blocked autophagic flux, as evidenced by the accumulation of LC3-II and SQSTM1/p62 and the decrease in LAMP-1 expression. Importantly, all these effects mediated by 15d-PGJ2 were abolished by cotreatment with the PPARγ antagonist GW9662. In conclusion, intranasal 15d-PGJ2 suppressed the growth of rat lactotroph PitNETs by inducing PPARγ-dependent apoptotic and autophagic cell death. Therefore, 15d-PGJ2 may be a potential new drug for lactotroph PitNETs.